Global issues for global citizens : (The World Bank, 2006)
Written by 27 World Bank experts, this book draws on the Bank's unique global capabilities and experience to promote an understanding of key global issues that cannot be solved by any one nation alone in an increasingly interconnected world. It describes the forces that are shaping public and private action to address these issues and highlights the Bank's own work in these areas. Covering four broad themes (global economy, global human development, global environment, and global governance), this comprehensive volume provides an introduction to today's most pressing global issues -- from poverty, conflict, and migration to climate change, international trade, education, health, and corruption. With its straightforward presentation of complex topics, use of real world examples, and suggestions for further reading on-line and in the literature, this unique volume will be an invaluable resource for students in international relations, global business, public policy, international development studies, sociology as well as other interested readers.